The evolution of ring current ion energy density and energy content during geomagnetic storms based on Van Allen Probes measurements. Issue 9 (26th September 2015) - Zhao, H.; Li, X.; Baker, D. N.; Fennell, J. F.; Blake, J. B.; Larsen, B. A.; Skoug, R. M.; Funsten, H. O.; Friedel, R. H. W.; Reeves, G. D.; Spence, H. E.; Mitchell, D. G.; et al.
Abstract Enabled by the comprehensive measurements from the Magnetic Electron Ion Spectrometer (MagEIS), Helium Oxygen Proton Electron mass spectrometer (HOPE), and Radiation Belt Storm Probes Ion Composition Experiment (RBSPICE) instruments onboard Van Allen Probes in the heart of the radiation belt, the relative contributions of ions with different energies and species to the ring current energy density and their dependence on the phases of geomagnetic storms are quantified. The results show that lower energy (<50 keV) protons enhance much more often and also decay much faster than higher‐energy protons. During the storm main phase, ions with energies <50 keV contribute more significantly to the ring current than those with higher energies; while the higher‐energy protons dominate during the recovery phase and quiet times. The enhancements of higher‐energy proton fluxes as well as energy content generally occur later than those of lower energy protons, which could be due to the inward radial diffusion. For the 29 March 2013 storm we investigated in detail that the contribution from O+ is 25% of the ring current energy content during the main phase and the majority of that comes from <50 keV O+. This indicates that even during moderate geomagnetic storms the ionosphere is still an important contributor to the ring current ions. Using the Dessler‐Parker‐Sckopke relation, the contributions of ring current particles to the magnetic field depression during this geomagnetic storm are also calculated. The results show that the measured ring current ions contribute about half of the Dst depression.